2019
DOI: 10.1103/physrevlett.123.245101
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cascade Rate Measured in a Collisionless Space Plasma with MMS Data and Compressible Hall Magnetohydrodynamic Turbulence Theory

Abstract: The first complete estimation of the compressible energy cascade rate |εC| at magnetohydrodynamic (MHD) and sub-ion scales is obtained in the Earth's magnetosheath using Magnetospheric MultiScale (MMS) spacecraft data and an exact law derived recently for compressible Hall MHD turbulence. A multi-spacecraft technique is used to compute the velocity and magnetic gradients, and then all the correlation functions involved in the exact relation. It is shown that when the density fluctuations are relatively small, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 56 publications
1
61
2
Order By: Relevance
“…(2017, 2018) and Andrés et al. (2019) employ the cascade model and evaluate contributions to the total cascade rate due to both compressive and incompressive channels. While these theories are of great interest, the experimental implementation is hampered by inability of measuring all quantities involved with single spacecraft, as well as limitation of applicability due to the additional approximations adopted (such as constant plasma beta).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017, 2018) and Andrés et al. (2019) employ the cascade model and evaluate contributions to the total cascade rate due to both compressive and incompressive channels. While these theories are of great interest, the experimental implementation is hampered by inability of measuring all quantities involved with single spacecraft, as well as limitation of applicability due to the additional approximations adopted (such as constant plasma beta).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…2018; Andrés et al. 2019). In the nonlinear regime, different scaling relations emerge (Lithwick & Goldreich 2001; Beresnyak, Lazarian & Cho 2005; Kowal & Lazarian 2007; Benzi et al.…”
Section: Introductionmentioning
confidence: 99%
“…These magnetic cavities, traveling with the plasma flows over a macrotime scale, can transport the hot trapped electrons away from the energy release source and shape the spectrum of compressional fluctuations on scales as small as the electron thermal gyroradius. In fact, the reported magnetic cavities were observed in the terrestrial magnetosheath, a location where compressional turbulence has been proposed and observed to be more important than in the solar wind plasmas 60 62 . Given the complicated dynamics of energy cascade and dissipation 63 , 64 indicated by the presence of distinct breakpoints in the turbulent magnetic spectrum at electron gyroscales 65 , 66 , the analyzed magnetic cavities may also be considered intermittent structures produced by the inhomogeneity of electron-scale turbulence cascade.…”
Section: Discussionmentioning
confidence: 99%
“…2018) and measurements in a collisionless space plasma using Magnetospheric Multiscale data in comparison with simulations of compressible HMHD turbulence (Andrés et al. 2019) indicate that neglecting the contribution of compressibility to the exact laws results in an underestimation of the total energy flux and dissipation rate, especially near the ion scale. However, in Andrés et al.…”
Section: Local Energy Transfer Analysismentioning
confidence: 99%
“…This effect was explicitly shown for two-dimensional simulations, for instance, in . Direct numerical simulations of compressible MHD turbulence (Andrés et al 2018) and measurements in a collisionless space plasma using Magnetospheric Multiscale data in comparison with simulations of compressible HMHD turbulence (Andrés et al 2019) indicate that neglecting the contribution of compressibility to the exact laws results in an underestimation of the total energy flux and dissipation rate, especially near the ion scale. However, in Andrés et al (2018) it was also found that except in cases in which the largest scales already On the other hand, a heuristic proxy has been recently introduced.…”
Section: Local Energy Transfer Analysismentioning
confidence: 99%